2014
DOI: 10.2478/amsc-2014-0056
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Coal Particle Size on Coal Adsorption and Desorption Characteristics

Abstract: Accurate testing coal isotherm can play a significant role in the areas of coal seam gas drainage, outburst control, CO 2 geo-sequestration, coalbed methane (CBM) and enhanced coalbed methane recovery (ECBM) etc. The effect of particle size on the CO 2 and CH 4 sorption capacity of bituminous coal from Illawarra, Australia was investigated at 35°C and at pressure up to 4 MPa. A unique indirect gravimetric apparatus was used to measure the gas adsorption and desorption isotherms of coal of different particle si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 22 publications
0
42
0
Order By: Relevance
“…As mentioned above, the tendency of coal to crush as a consequence of mining operations underground constitutes a factor that can activate a specific surface area (SSA) of coal and lead to an increase in the amount of the adsorbed gas . The influence of coal particle size on the sorption capacity as regards mine gases has been previously studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the tendency of coal to crush as a consequence of mining operations underground constitutes a factor that can activate a specific surface area (SSA) of coal and lead to an increase in the amount of the adsorbed gas . The influence of coal particle size on the sorption capacity as regards mine gases has been previously studied.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of coal particle size on the sorption capacity as regards mine gases has been previously studied. Yet most of these measurements were performed with the use of carbon dioxide and methane in respect to enhanced coalbed methane recovery or with the use of single gases, eg, propylene and acetylene as an adsorbate . In turn, studies on the sorption of the mixture of ethylene, propylene, propane, and ethane have been previously performed but only on coals with the grain size of 0.5 to 0.7 mm.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that the high gas content of the coal seam also has an impact on the excavation of the return airway. Regarding this, the comprehensive gas flow characteristics and the hard-to-drain problem of the coal seam are also investigated [32][33][34], and the gas problem will not be detailed in this paper.…”
Section: Field Measurementsmentioning
confidence: 99%
“…deviation of sorption and desorption isotherms shows no dependence on coal rank. Zhang et al (2014) found that the sorption capacity and hysteresis of coal can be influenced with coal particle sizes. The numerical simulation of Yang et al (2010) shows that the gas drainage of carbon dioxide injection is better than that of nitrogen injection, but the research of Fang et al (2009) showed that the injected carbon dioxide may reduce the coal permeability, which is the disadvantage of methane emission.…”
Section: Introductionmentioning
confidence: 99%